A textbook of physical chemistry - Negi, A.S (New Age International, 2007)
The revised second edition of the book is intended to meet the requirement of the students of science, engineering and other professional courses at the undergraduate level. It has been planned strictly in line with the syllabi of various Indian Universities who have adopted the new ten-plus-two-plus-three pattern of education. A new chapter on Macromolecules has been added, thus making a total of 27 chapters in the revised edition. Chapters on Chemical Equilibrium, Colligative Properties, Atomic Structures, Chemical Bonding have been thoroughly reshuffled and rewritten. Chapter 25 has been rearranged and divided into two chapters viz., Molecular Spectroscopy and Electrical and Magnetic Properties. New sections have been added to chapters on Gaseous State, Colligative Properties, Electrolytic Conduction, Ionic Equilibria, Chemical Kinetics, Atomic Structure and Chemical Bonding. Other chapters have also been modified and redesigned. The subject matter has been given in a logical, simple and lucid language. The main aim has been on self learning. Some more diagrams and illustrations have been added in this edition for explaining the fundamentals of the subject. Conventional problems in the earlier edition have been dropped, but general and objective type problems are retained. A considerable number of worked-out problems have been included in most of the chapters. These would expose the students to applications of various concepts and fundamentals of the subject. The revised text largely uses SI units but CGS units have been retained in those cases where the SI units have not as yet been fully appreciated. We have attempted to present a revised text that effectively provides clean, accurate and balanced views on various topics to grasp the fundamentals of the subject more clearly, comprehensively and concretely. The book should meet the requirements of students.